1988
DOI: 10.1212/wnl.38.7.1041
|View full text |Cite
|
Sign up to set email alerts
|

Microdysgenesis in resected temporal neocortex

Abstract: Fifty patients underwent superficial temporal lobectomy for intractable temporal lobe epilepsy. Total cure rate was 52%, and significant improvement was achieved in 88%. Cytoarchitectural changes in gray and white tissue were analyzed under light microscopy. Neuronal dysgenesis was correlated with the duration of seizure disorder, age of onset, and other etiologic factors, and with clinical outcome. Temporal lobes from 33 neurologically normal autopsy brains which were age- and sex-matched with patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
3
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(154 citation statements)
references
References 0 publications
8
141
3
2
Order By: Relevance
“…In the context of temporal lobe epilepsy, interstitial neurons within white matter are usually described as heterotopic (Meencke & Janz, 1984;Hardiman et al 1988;Armstrong, 1993;Wolf & Weistler, 1993;Mischel et al 1995) and thought to represent one element of a group of developmental disorders frequently referred to as cortical dysplasia (Taylor et al 1971), glioneuronal hamartia (Wolf & Weistler, 1993), microdysgenesis (Meencke & Janz, 1984;Hardiman et al 1988;Armstrong, 1993) or heterotopia . Rojiani et al (1996) found that these 'residual ⁄ heterotopic neurons' were significantly more numerous in temporal than in frontal or occipital cortex, and concluded that they represent interstitial remnants of the subplate which have failed to undergo programmed cell death.…”
Section: Revival Of Early Concepts In Current Developmental and Neuromentioning
confidence: 99%
“…In the context of temporal lobe epilepsy, interstitial neurons within white matter are usually described as heterotopic (Meencke & Janz, 1984;Hardiman et al 1988;Armstrong, 1993;Wolf & Weistler, 1993;Mischel et al 1995) and thought to represent one element of a group of developmental disorders frequently referred to as cortical dysplasia (Taylor et al 1971), glioneuronal hamartia (Wolf & Weistler, 1993), microdysgenesis (Meencke & Janz, 1984;Hardiman et al 1988;Armstrong, 1993) or heterotopia . Rojiani et al (1996) found that these 'residual ⁄ heterotopic neurons' were significantly more numerous in temporal than in frontal or occipital cortex, and concluded that they represent interstitial remnants of the subplate which have failed to undergo programmed cell death.…”
Section: Revival Of Early Concepts In Current Developmental and Neuromentioning
confidence: 99%
“…Focal cortical dysplasia has been reported in 6-20% of patients who undergo temporal resection (106,107). On MRI, the most definite abnormality is the presence of cortical thickening associated with a poor differentiation of the gray-white matter (108,109).…”
Section: Cortical Dysplasiamentioning
confidence: 99%
“…They are often associated with patients having severe epilepsies or cognitive defects (Mischel et al, 1995;Porter et al, 2003). Thus, cortical malformations are present in Ͻ24% of all epilepsy patients but are found in 40% of cases that are refractory to treatment (Hardiman et al, 1988;Farrell et al, 1992). Anatomical and functional studies in rodents with cortical malformations suggest that ectopic neurons form afferent and efferent connections with adjacent cortex (for review, see Chevassus-Au- , indicating that heterotopias are integrated within cortical networks.…”
Section: Introductionmentioning
confidence: 99%